A novel robust Virtual Reference Feedback Tuning approach for minimum and non-minimum phase systems. (September 2021) - Chiluka, Suresh Kumar; Ambati, Seshagiri Rao; Seepana, Murali Mohan; Babu Gara, Uday Bhaskar
Abstract: In real-world applications, it is often desired that the design of a closed-loop system must attain not only high performance but also robustness. This paper presents a novel robustness-based formulation for control for discrete time minimum and non-minimum phase systems using the Virtual Reference Feedback Tuning (VRFT) framework. The proposed idea is to design robust lower and higher order Proportional Integral and Derivative (PID) controller using Maximum Sensitivity ( M s ) based closed-loop reference model by minimization of the VRFT objective function (J VR ) The efficacy of the approach is verified on various systems in simulation and also demonstrated on the Temperature Control Process and Level Control Process experimental setups. The proposed VRFT approach provides improved performance and robustness for set point tracking and disturbance rejection. Also, the proposed approach ensures stability and specific robustness of the closed-loop system. Further, the fragility of the controller is investigated for perturbations in the controller parameters. Highlights: A novel VRFT approach is proposed based on specific robustness. Fragility and robustness analysis of the closed loop system is performed. The proposed method gives improved performance in simulation examples. Experimental validation with temperature control and level control processes. The proposed method enables to design high, medium and low robust controllers.